Pengaruh Citra Merek Terhadap Minat Beli Produk Erigo - Siti Mabrur Rachmah (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
The purpose of this study is to determine the effect of Brand Image on Purchase Intention Erigo product. This research uses quantitative research type. The data source of this research is primary data by using consumer and buyer of Erigo as sample. Data were collected by accidental sampling with 100 respondents of Erigo. This study uses simple regression analysis. The findings of this study indicate that the Brand Image significantly influence the Purchase Intention of Erigo